PENGARUH MODEL REALISTIC MATHEMATICS EDUCATION BERBANTUAN APLIKASI DESMOS TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Dita Khairani Hasibuan; Eva Margharetha Saragih (Universitas Islam Sumatera Utara, 2026)
This study was motivated by the researcher’s commitment to improving the problem-solving skills of students at Meranti State Senior High School 1. The aim of this study was to determine the effect of the Realistic Mathematics Education model, supported by the Desmos application, on the problem-solving skills of Year 10 students at Meranti State Senior High School 1. The study employed a quasi-experimental design, specifically a two-group pre-test–post-test design. The population in this study comprised all Year 10 classes X-5 and X-6, selected using cluster random sampling. The subjects of this study were the students of Year 10 class X-6, serving as the experimental group using the Realistic Mathematics Education model supported by the Desmos application, and Year 10 class X-5, serving as the control group using the direct instruction model. The material used in this study was central tendency statistics: mean, median and mode of single data sets. Following the completion of the lessons, a post-test was administered, yielding an average score of 75.1 for the experimental class and 56.8 for the control class. The t-test results indicate a significant effect of the Realistic Mathematics Education model supported by the Desmos application on problem-solving skills in the statistics module for Class X at State Senior High School 1 Meranti.